Kajian Kerusakan Tablet Hisap Spirulina Selama Penyimpanan - Iriani Setyaningsih; Wini Trilaksani; . Desniar; Emma Masruroh; Ria Fahleny; Vatin Tri Gentini (Institut Pertanian Bogor, 2014)
Spirulina is a microalgae have a high nutrient content and bioactive compound were good for health. This microalgae can be cultivated indoor or outdoor as needed. One of the applications of Spirulina is for lozenges. The purpose of this study is determine the effect of packaging and shelf life of Spirulina lozenges on the growth of bacteria and fungi. This microalgae can be cultivated indoor or outdoor as needed. One of the applications of Spirulina is for lozenges. Bacteria and fungi still grow on the Spirulina lozenge which packaged using alumunium foil and plastic bottle. However bacteria and fungi total on Spirulina lozenge during storage on 8 weeks are not different.